Nahrain Mobile Learning System (NMLS) - Abd Al-Kareem, Mahmood Sami; AL-Mukhtar, Mumtaz (Al-Khwarizmi Engineering Journal, 2011)
The work in this paper involves the planning, design and implementation of a mobile learning system called Nahrain Mobile Learning System (NMLS). This system provides complete teaching resources, which can be accessed by the students, instructors and administrators through the mobile phones. It presents a viable alternative to Electronic learning. It focuses on the mobility and flexibility of the learning practice, and emphasizes the interaction between the learner and learning content. System users are categorized into three categories: administrators, instructors and students. Different learning activities can be carried out throughout the system, offering necessary communication tools to allow the users to communicate with each other through forums, SMS and e-mails. NMLS platform is based on 3G mobile phone technology and adopted WAP as a solution for the system platform. The NMLS framework is based on three layers, which are presentation layer, business logic layer and data layer.